Blood-loss Management in Spine Surgery. Issue 2 (15th January 2018) - Bible, Jesse E.; Mirza, Muhammad; Knaub, Mark A.
Abstract : Substantial blood loss during spine surgery can result in increased patient morbidity and mortality. Proper preoperative planning and communication with the patient, anesthesia team, and operating room staff can lessen perioperative blood loss. Advances in intraoperative antifibrinolytic agents and modified anesthesia techniques have shown promising results in safely reducing blood loss. The surgeon's attention to intraoperative hemostasis and the concurrent use of local hemostatic agents also can lessen intraoperative bleeding. Conversely, the use of intraoperative blood salvage has come into question, both for its potential inability to reduce the need for allogeneic transfusions as well as its cost-effectiveness. Allogeneic blood transfusion is associated with elevated risks, including surgical site infection. Thus, desirable transfusion thresholds should remain restrictive.